Chemical identification of single ultrafine particles using surface-enhanced infrared absorption - Huck, Christian; Tzschoppe, Michael; Neubrech, Frank; Pucci, Annemarie (Physical review applied, 2019)
In the past decade, it has been demonstrated that surface-enhanced infrared absorption (SEIRA) is a powerful method to enhance vibrational signals of thin molecular layers. Much less attention has so far been given to the possibility of using SEIRA for the detection and characterization of nanometer-sized particles, such as ultrafine dust particles. Here, we report on SEIRA measurements demonstrating that even one single particle with a deeply subwavelength dimension of less than 100 nm can be detected and chemically characterized with standard infrared microspectroscopy. Our approach is based on plasmonic resonances of bowtie-shaped Au apertures that are designed to extraordinarily enhance the material-specific phononic excitations of a nanometer-sized silica particle. We show that the bowtie geometry is especially suited for single-particle spectroscopy, as it combines the advantage of an intense electromagnetic hot spot, the size of which can be adjusted to the particle dimension, with easy positioning of ultrafine dust particles inside that hot spot. In agreement with numerical calculations, we show that a detection limit in terms of a particle diameter of less than 20 nm can be achieved, which corresponds to a ratio of the diameter to the vacuum wavelength below 0.002. Our approach offers the possibility of analyzing infrared bands from tiniest particles and thus paves the way toward SEIRA-based devices that can sense ultrafine dust.